An empire on trial race, murder, and justice under British rule, 1870 - 1935 - Wiener, Martin J. 1941- (Cambridge Univ. Press, 2009)
'An Empire on Trial' explores the issue of interracial homicide in the British Empire during its height - examining these incidents and the prosecution of such cases in each of seven colonies scattered throughout the world.
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1870-1935; Geschichte; Kolonie; Criminal justice, Administration of -- Great Britain -- Colonies -- History; Racism -- Great Britain -- Colonies; Strafjustiz; Rassenfrage; Mord; Rassismus; Tötung; Großbritannien; Great Britain -- Colonies -- Race relations; Great Britain -- Colonies -- History -- 19th century; Great Britain -- Colonies -- History -- 20th century